Mixed methods study to develop the content validity and the conceptual framework of the electronic patient-reported outcome measure for vascular conditions. Issue 8 (11th August 2020) - Aber, Ahmed; Phillips, Patrick; Lumley, Elizabeth; Radley, Stephen; Thomas, Steven M; Nawaz, Shah; Jones, Georgina; Michaels, Jonathan
Abstract : Objective: The aim of this paper is to describe the stages undertaken to generate the items and conceptual framework of a new electronic personal assessment questionnaire for vascular conditions. Design: A mixed methods study: First a survey of vascular clinicians was completed to identify the most common conditions treated in vascular clinics and wards. Quantitative systematic reviews were done to identify validated patient-reported outcome measures (PROMs) for direct inclsuion in the new instrument. However, due to scarcity of validated PROMs, the items of the new instrument were mainly based on a large qualitative study of patients and systematic reviews of the qualitative evidence . This was followed by a quantitative clinicians' consensus study and, finally, a qualitative face validity study with patients. Participants: Vascular patients participated in the primary qualitative study and the face validity study. In the qualitative study, 55 patients were interviewed, and for the face validity, 19 patients gave feedback. Twelve clinicians completed the survey and 13 completed two cycles of the clinicians' consensus study. Results: The items and scales in the electronic personal assessment questionnaire for vascular conditions (ePAQ-VAS) were generated based on the results of five systematic reviews evaluating existing PROMs for possible inclusion in ePAQ-VAS, five systematic reviews of qualitative evidence, a primary qualitative study involving 55 patients and clinicians' input. One hundred and sixty-eight items were initially generated, of which 59 were eliminated by the expert panel due to repetition. The instrument was divided into one generic and three disease-specific sections (abdominal aortic aneurysm, carotid artery disease and lower limb vascular conditions). In each section, items were grouped together into putative scales. Fifty-five items were grouped across eight scales; the remaining items were kept as individual items, because of relevance to service users. Conclusions: This multidimensional electronic questionnaire covers the most common vascular conditions. This is particularly important for patients presenting with mixed symptoms or multiple conditions. This tool captures symptomatology, health related quality of life (HRQoL) and other clinically relevant data, such as experience with services and comorbidities.